Photon Statistical Properties Emitted from Single Molecule Derived from Generating Function Method (Journal of Atomic and Molecular Sciences, 2016)
In this paper, we summarize the photon emission statistical properties ofsingle molecule system, using the recently developed generating function method.Through the introduce of one or double “auxiliary” variables, we can investigate thefirst moment and second moment of photon emission statistics driven by differentexternal fields, such as the line shapes and Mandel's Q parameters, the photon emissionprobabilities, the probability distribution of time between successive emission, thewaiting time and the waiting time distribution, the cross correlation, the joint probabilities,etc. Among, the first moment of photon statistics and the experimental resultsof optical amplification are in good agreement.
Keywords: Two-Level System; Generating Function; Photon Counting Statistics.